Characteristics of Atmospheric Inorganic Nitrogen Wet Deposition in Coastal Urban Areas of Xiamen, China - Yao Feng; Shuhui Zhao; Shanshan Wang; Qi Lin; Yang Luo; Suqing Xu; Hang Yang; Jun Shi; Miming Zhang; Liping Jiao; Jinpei Yan (Atmosphere, 2021)
To evaluate the impact of increasing atmospheric nitrogen deposition input to the coastal ecosystem, measurements were conducted to analyze the inorganic nitrogen wet deposition to Xiamen Island during April to August in 2014. Using ion chromatography and shown to contain main nine water-soluble ions—including Na+, NH4+, K+, Mg2+, Ca2+, Cl−, NO−, NO3−, and SO42−—we analyzed the composition of the wet deposition sample and verified the contribution of different ions to the different sources. The results showed that the mean NO3−-N and NH4+-N concentration in rainfall for five months was 4.55 ± 5.15 mg·L−1 (n = 31) and 1.20 ± 1.16 mg·L−1 (n = 33), respectively. Highest NO3−-N (74.65 mg·N·L−1) and NH4+-N (16.06 mg N·L−1) values were both observed in May. Maximum NO3−-N deposition (507.5 mg·N·m−2) was also in May, while the highest NH4+-N deposition (99.8 mg·N·m−2) was in June. The total inorganic wet nitrogen flux during sampling period was 11.1 kg·N·ha−1. The HYSPLIT backward air masses trajectory and USEPA PMF model was used, as the composition of the air masses passing over the sample area were impacted from three sources: fertilizers and biomass combustion, formation of secondary aerosol, and Marine aerosols. The concentration ratio of SO42− and NO3− in ranged between 0.5 and 3 in rainfall samples with an average of 1.34, suggesting that the contribution from vehicle exhaust to air pollution in the sample area is increasing. Long-term continuous monitoring of wet deposition in this region needs to be expanded to fully understand the impacts of human activity on air quality and to quantify N deposition to local marine ecosystems.